The Role of Radiologic Imaging in Diagnosing Complications of Video-Assisted Thoracoscopic Surgery - Mason, Andrew C.; Krasna, Mark J.; White, Charles S. (Chest, 1998)
To examine the role of radiologic imaging in evaluating complications of video-assisted thoracoscopic surgery. Retrospective review of radiographic and clinical data. Tertiary referral hospital. All patients who underwent thoracoscopy at the University of Maryland Hospital between July 1990 and June 1994. A total of 260 procedures were performed on 239 patients. Imaging studies performed before, during, and after surgery in cases in which complications occurred were reviewed by two thoracic radiologists. A randomly selected group of 22 CT scans from uncomplicated cases were used as control subjects. Complications occurred in 24 (9.2%) of the 260 thoracoscopic procedures. Intraoperative complications developed in 14 (5.4%) patients. Ten of the 14 patients had an obliterated pleural space that prevented access of the trocars and videoscope. Preoperative imaging showed significant pleural thickening or calcifications in seven of these ten patients. Other intraoperative complications were malposition of the double-lumen endotracheal tube (n=2) and dislodgement of a localizing needle-wire (n=2). In 8 (3.1%) patients, radiographically evident postoperative complications developed; these complications included prolonged air leak, empyema, recurrent pneumothorax, pulmonary edema, and pneumonia. Pleural calcification or thickening that is found on preoperative studies may help predict difficulty in inserting the thoracoscopic instruments but also can be seen on preoperative CT scans in uncomplicated cases. Thoracic CT scans may fail to predict complete pleural symphysis.